THE CELLULAR RIVERS OF LIFE: A COMPREHENSIVE REVIEW OF THE CORPUSCULAR ELEMENTS OF BLOOD - Asatullyev Rustam Baxtiyorovich,; Kalandarova Marjona Turakulovna, (TADQIQOTLAR, 2026)
Abstract:  Blood,  the  liquid  connective  tissue  that  circulates  throughout  the human body, is composed of two main components: plasma (the liquid matrix) and formed  elements  (corpuscles).  The  corpuscular  elements-erythrocytes  (red  blood cells), leukocytes (white blood cells), and thrombocytes (platelets)-perform essential functions that sustain life. Erythrocytes are responsible for oxygen transport, facilitated by the hemoglobin molecule; leukocytes constitute the cellular arm of the immune system,  defending  against  pathogens  and  malignancies;  and  thrombocytes  mediate hemostasis, preventing bleeding after vascular injury. This article provides a systematic review  of  the  morphology,  physiology,  production  (hematopoiesis),  and  clinical significance  of  each  corpuscular  element.  Special  attention  is  given  to  quantitative disorders (anemias, leukopenias, thrombocytopenias) and qualitative disorders (sickle cell disease, leukocyte adhesion deficiency, platelet function defects). The article also discusses  laboratory  assessment,  including  complete  blood  count,  peripheral  blood smear, and advanced flow cytometry. The review concludes with emerging therapeutic applications, including blood transfusion, hematopoietic stem cell transplantation, and platelet-rich plasma therapy.